An investigation of pile diameter influence in the bearing capacity on Dynamic Load Test (DLT) - Bernardes, G. P.; Andreo, C. S.; Goncalves, C. (A A Balkema Publishers, 2000)
During the construction of five residential buildings in the city of Taubate, State of São Paulo, it was possible to carry out one comprehensive investigation of the behavior of precast concrete piles in clay shales. This paper describes the results of Dynamic Load Tests (DLT's) executed in three piles with different diameters and with the same embedded length. The tests were monitored using the PDA(R) (Pile Driving Analyzer) and the pile top displacement was measured by pencil and paper procedure. From the curves of RMX versus DMX resulted from CASE(R) method, CAPWAPC(R) analyses were made for signals where the maximum mobilized soil resistance was verified. The results were compared with the predicted bearing capacity using the semi-empirical method of Decourt & Quaresma (1978) and Decourt (1982) based on SPT values and the description of the soil profile. Some comments related to the values of quake and damping used for clay shales in the analyses are also presented.